Pattern of Target Organ Damage among Hypertensive Patients with Chronic Kidney Disease as Compared with Hypertensive Patients without Chronic Kidney Disease - Oluwaseye Michael Oladimeji; Godiya Ishaya Dare; John Okopi; Alaba Busola Oladimeji; Anthony G. Kweki; Abisola Iyayi; Ugoeze Nneka Iloeje; Bilqis Ibrahim; Atinuke Richard; Oluwaseun Okunuga; Ramon Moronkola; Adeola Ajibare; et al. (Nigerian Journal of Medicine)
Background: Patients with chronic kidney disease (CKD) have been shown to have high prevalence of hypertension, which results in high burden of target organ damage (TOD) with associated high morbidity and mortality. It has been established that majority of CKD patients do not necessarily progress to end-stage renal disease, but rather the high mortality rate has been attributed to the high burden of cardiovascular disease. Furthermore, traditional cardiovascular risk factors such as hypertension have consistently been attributed to high incidence and prevalence of TOD. Therefore, assessment and management of TOD is very essential among CKD patients. The aim of the study was to assess the pattern and prevalence of TOD among hypertensive patients with CKD attending the nephrology clinic at Lagos State University Teaching Hospital. Materials and Methods: A cross-sectional comparative study was carried out on 172 CKD subjects with hypertension and 156 hypertensive subjects without CKD as controls. Subjects were assessed for the presence of TOD which included left ventricular hypertrophy (LVH), atrial fibrillation, ischaemic heart disease (IHD), congestive cardiac failure, stroke, and hypertensive retinopathy using relevant investigating tools. Results: A total of 328 participants were studied, made up of 172 CKD subjects and 156 hypertensive control subjects without CKD. The mean age of CKD subjects and controls were 51.38 ± 15.86 years and 54.42 ± 12.72 years (t = −1.956, 95% confidence interval = −6.107–0.030, and P = 0.052), respectively, and the difference was not significant. The mean systolic blood pressure (BP) for CKD subjects and controls was 145.69 ± 24.39 mmHg and 146.99 ± 26.53 mmHg (t = −0.463 and P = 0.644), respectively, and there was no significant difference. The prevalence of TOD was significantly higher among subjects as compared to controls which are as follows: overall TOD was 66.9% versus 35.9% (odds ratio [OR] = 3.6, P < 0.001), LVH was 40.7% versus 23.1% (OR = 2.29, P = 0.001), left ventricular strain pattern was 14% versus 6.4% (OR = 2.39, P = 0.025), IHD was 23.3% versus 12.8% (OR = 2.06, P = 0.015), and stroke was 8.7% versus 3.8% (OR = 2.39, P = 0.072), respectively. Advanced hypertensive retinopathy was present in 7.8% of subjects only, and there was a weak positive correlation between hypertensive retinopathy and severity of hypertension. Conclusions: This study showed high prevalence of TOD among CKD subjects with hypertension compared to hypertensive subjects without CKD, which may likely worsen the outcome in patients with CKD. The high frequency of uncontrolled BP and advanced CKD significantly contributed to the high frequency of TOD. Therefore, early identification and management of hypertension will be beneficial in reducing the high burden of TOD among CKD patients.